THE USE OF NEW REAGENT KITS FOR DETECTION AND DESCRIPTION OF ADDITIONAL ALLELES - M. A. Loginova; N. P. Trophimova; I. V. Paramonov (Вестник трансплантологии и искусственных органов, 2011)
During the screening typing of recruited volunteers with Volga Federal District for unrelated hematopoietic stem cell registry on the loci (HLA)-A, B, DRB1, DRB345 in sample No 1758 identified a new allele at locus A. The use of basic kit AlleleSEQR HLA-A Sequencing in combination with HARP – A2F98A allowed to determine the genotype of this sample – А*30:01:01, a new allele А*25, В*13, 44, DRB1*03, 09, DRB3*02, DRB4*01.